Eggerthella lenta Bacteremia in a Patient With Adenocarcinoma of the Rectosigmoid Colon: A Case Report and Review of Management Challenges - Mahnoor Arshad; Shitij Shrivastava; Zoraize M. Athar; Sabirah N. Kasule; Sridhar S. Chilimuri; Cosmina B. Zeana (Annals of Internal Medicine: Clinical Cases)
We present a case of sepsis secondary to Eggerthella lenta bacteremia in a patient with newly diagnosed adenocarcinoma of the rectosigmoid colon. Management involved antibiotic escalation from piperacillin-tazobactam to meropenem, resulting in resolution of sepsis and clearance of the bacteremia. This case highlights the association between E lenta bacteremia and gastrointestinal malignancies. It also emphasizes the importance of timely diagnosis and appropriate antibiotic therapy.